2020
DOI: 10.1002/hup.2761
|View full text |Cite
|
Sign up to set email alerts
|

Safety and cardiovascular effects of multiple‐dose administration of aripiprazole and olanzapine in a randomised clinical trial

Abstract: ObjectiveTo assess adverse events (AEs) and safety of aripiprazole (ARI) and olanzapine (OLA) treatment.MethodsTwenty‐four healthy volunteers receiving five daily oral doses of 10 mg ARI and 5 mg OLA in a crossover clinical trial were genotyped for 46 polymorphisms in 14 genes by qPCR. Drug plasma concentrations were measured by high‐performance liquid chromatography tandem mass spectrometry. Blood pressure (BP) and 12‐lead electrocardiogram were measured in supine position. AEs were also recorded.ResultsARI d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
(94 reference statements)
0
10
0
Order By: Relevance
“…The incidence of akathisia was higher in DRD3 rs6280 Ser/Ser homozygotes vs. Gly allele carriers and asthenia appeared more often in DRD2 rs1799732 G/- subjects vs. G/G homozygotes ( 81 ).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The incidence of akathisia was higher in DRD3 rs6280 Ser/Ser homozygotes vs. Gly allele carriers and asthenia appeared more often in DRD2 rs1799732 G/- subjects vs. G/G homozygotes ( 81 ).…”
Section: Resultsmentioning
confidence: 90%
“…Aripiprazole was associated with a higher diastolic blood pressure lowering effect in healthy volunteers participating in a phase I trial who presented a polymorphism in the serotonergic 5HT2A receptors (HTR2A rs6313C genotype) and one in the α2 adrenergic receptors gene (ADRA2A rs1800544 C/C vs. T/T or C/G) ( 81 ). This observation may be explained by the participation of alpha-2 receptors and 5HT2A receptors in vasodilatation and sympathetic cardiovascular regulation ( 81 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies proposed that possessing Stasis BC is significantly associated with hyperlipidaemia, atherosclerosis, coronary heart disease, or coronary artery disease [38][39][40]. Several studies demonstrated that olanzapine is a relatively unsafe drug, especially for patients who have coronary heart disease [41][42][43][44]. In addition, some research showed that antipsychotic drug use is associated with acute myocardial infarction and stroke [45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…Thanks to the availability of these data (i.e., the outcomes of the clinical trials) and the informed consent of the healthy volunteers, a valuable source of information is available for pharmacogenetic research. In the last decade, our group contributed to the expansion of available pharmacogenetic knowledge with numerous publications [36,37,[41][42][43][44][45][46][47].…”
Section: The Genotrial Projectmentioning
confidence: 99%